2018
DOI: 10.1039/c8en00063h
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and impacts of polyvinylpyrrolidone (PVP) capped metal oxide nanoparticles on Daphnia magna: role of core composition and acquired corona

Abstract: A key hypothesis in nanosafety assessment is that the NP core chemistry and eco-corona are primary factors controlling toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…It is extremely likely that these secreted biomolecules can adsorb onto NM surfaces creating an evolving eco‐corona thereby affecting the stability, identity and toxicity of the NMs toward D. magna . Indeed, it has been shown that both amino and carboxylic acid functionalized PS NMs and polyvinylpyrrolidone‐capped ZnO and CeO 2 NMs agglomerate when incubated in conditioned medium, with longer incubation times leading to larger NM sizes which increased their uptake by D. magna and resultant toxicity . Given that zooplankton such as D. magna feed on algae, it is important to understand the potential role of algal secretions also in NM eco‐coronas.…”
Section: The Eco‐coronamentioning
confidence: 99%
“…It is extremely likely that these secreted biomolecules can adsorb onto NM surfaces creating an evolving eco‐corona thereby affecting the stability, identity and toxicity of the NMs toward D. magna . Indeed, it has been shown that both amino and carboxylic acid functionalized PS NMs and polyvinylpyrrolidone‐capped ZnO and CeO 2 NMs agglomerate when incubated in conditioned medium, with longer incubation times leading to larger NM sizes which increased their uptake by D. magna and resultant toxicity . Given that zooplankton such as D. magna feed on algae, it is important to understand the potential role of algal secretions also in NM eco‐coronas.…”
Section: The Eco‐coronamentioning
confidence: 99%
“…Uptake of NPs is a crucial factor in assessing the effects of NPs [12]. When Ag NPs are associated with algae, it is possible for them to transfer up the food web [49].…”
Section: Introductionmentioning
confidence: 99%
“…50,51,55 This could lead to unforeseen toxicities if the POPs form part of a dynamic corona which may then "unload" into various organisms which are normally exposed at lower doses based on equilibrium partitioning, or indeed are not exposed at all to these pollutants in normal settings. 35 Importantly using a common freshwater organism model it is possible to compliment the metabolite corona data with the protein corona from the same organism; 5,150 such studies with other model organisms may help pave the way to uncover similarities in behavior between the two corona classes, particularly with organisms from different environments.…”
Section: Metabolite Eco-coronamentioning
confidence: 99%